Pengaruh Penggunaan Media Audio Visual Terhadap Kemampuan Menyimak Mata Pelajaran Bahasa Indonesia - Alifia Khoerunnisa; Mas Roro Diah Wahyu Lestari (Universitas Muhammadiyah Kuningan, 2024)
This research was motivated by the low level of listening ability in Indonesian language subjects and the lack of active participation in learning activities. This research also aims to determine the effect of using audio-visual media on the ability to listen to Indonesian language subjects. The method used in this research was quasi-experimental with a sample size of 29 students at SDN Karang Satria 02 for the 2022/2023 academic year, even semester, with a one group pretest posttest research design. Data collection techniques are documentation and tests. The research results can be seen from the results of calculations using the Paired Sample t-test type and the t test results obtained with a t value of -8.175. With a sig (2-tailed) value of 0.000 and a significance level of 0.05. This means that the significance of 0.000 is less than 0.05 so that is H0 rejected and Ha is accepted. So it can be concluded that there is an influence of the use of audio-visual media on the ability to listen to Indonesian language subjects in class V of SDN Karang Satria 02. The results of this research are expected to be useful to related parties who can use them, such as school principals, teachers, students and future researchers.